2009
DOI: 10.1088/1742-6596/171/1/012061
|View full text |Cite
|
Sign up to set email alerts
|

K and B meson mixing in warped extra dimensions with custodial protection

Abstract: After a brief theoretical introduction of the warped extra-dimensional model with custodial protection the results of [1] are presented. In this work we analyze the impact of Kaluza-Klein (KK) gauge boson modes on ∆F = 2 observables, for the first time considering the full operator basis and including NLO renormalization group running. It is pointed out that the dominant contribution in the B-system does not come from the KK gluon, but that contributions from KK excitations of the weak gauge bosons are competi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 49 publications
(67 reference statements)
0
10
0
Order By: Relevance
“…K, B and D mesons. Signatures of this class of models along with the correlations generated by the same in K and B physics have been studied in great detail by [21][22][23][24][25][26][27][28][29][30]. They have extracted the flavour structure of these models as well as the fermion mass hierarchy which is consistent with current experimental bounds.…”
Section: Introductionmentioning
confidence: 70%
“…K, B and D mesons. Signatures of this class of models along with the correlations generated by the same in K and B physics have been studied in great detail by [21][22][23][24][25][26][27][28][29][30]. They have extracted the flavour structure of these models as well as the fermion mass hierarchy which is consistent with current experimental bounds.…”
Section: Introductionmentioning
confidence: 70%
“…As an outcome of our analysis we have shown that while Higgs FCNCs have an impact on ǫ K as was already pointed out in [6], their contribution for a brane Higgs is dwarfed by the contribution of KK gluons even in the most favorable scenario for the Higgs contributions. For a brane Higgs scenario with reasonable choices fundamental Yukawa couplings the bound on the KK scale implied by the presence of tree-level Higgs exchanges is found to be 5 − 7 TeV, to be compared to the corresponding bounds for KK gluon exchange that are given by M KK (9 TeV − 14 TeV) for g * = 3 and M KK (19 TeV − 32 TeV) for g * = 6 (see also [4,7,20]).…”
Section: Discussionmentioning
confidence: 98%
“…20) and their numerical values at the lattice scale µ L = 2.0 GeV are given by[13] B 2 = 0.679 , B 3 = 1.055 , B 4 = 0.810 , B 5 = 0.562 . (3.21)…”
mentioning
confidence: 99%
“…On the other hand SM-like value of S ψφ will open the road for large enhancements of these branching ratios that could be tested by KOTO at J-Parc and NA62 at CERN, respectively. Reviews of our work on the RSc model appeared in [40,41,36,42,43,44].…”
Section: Discussionmentioning
confidence: 99%